CHANGES IN CHOROIDAL THICKNESS AFTER PANRETINAL PHOTOCOAGULATION IN PATIENTS WITH TYPE 2 DIABETES. Issue 4 (April 2015) - Zhu, Ying; Zhang, Ting; Wang, Keyan; Xu, Gezhi; Huang, Xin
Abstract : Purpose: To investigate the changes in choroidal thickness (CT) in the macular and photocoagulated areas of patients with diabetic retinopathy after panretinal photocoagulation (PRP) using enhanced depth imaging optical coherence tomography. Methods: Patients with severe nonproliferative diabetic retinopathy or early proliferative diabetic retinopathy who needed PRP were included in this study. Choroidal thickness in the macula and the photocoagulated area was measured with enhanced depth imaging optical coherence tomography at baseline, 1 month, and 3 months after PRP. Results: The mean subfoveal CT increased significantly at 1 month (318.0 ± 76.4 μ m, P < 0.001) and 3 months (317.4 ± 75.3 μ m, P < 0.001) after PRP when compared with baseline (307.2 ± 70.7 μ m). The mean CT in the photocoagulated area decreased significantly from 227.5 ± 45.0 μ m to 206.9 ± 41.1 μ m ( P < 0.001) at 1 month and 206.0 ± 41.4 μ m ( P < 0.001) at 3 months after PRP. The subgroup analysis showed similar trends of CT changes in patients with or without diabetic macular edema. The mean change in CT was not statistically significantly correlated with the mean change in best-corrected visual acuity after PRP. Conclusion: In patients with severe nonproliferative diabetic retinopathy or early proliferative diabetic retinopathy, the mean CT increased significantly in the macular area and decreased significantly in the photocoagulated area after PRP. The results might reflect a redistribution of choroidal blood flow, which may be critical for retinal metabolism. Abstract : In patients with severe nonproliferative diabetic retinopathy or early proliferative diabetic retinopathy who needed panretinal photocoagulation, the choroid significantly thickened in the macular region and significantly thinned in the photocoagulated area at 1 month and 3 months after panretinal photocoagulation.